Ultra-fast liquid chromatography detection of β-N-methylamine-l-alanine and its isomers in cycad seeds and cyanobacterial symbionts for neurotoxic risk assessment - Uthra, Chandrabose; Shunmugam, Sumathy; Nagaraj, Karuppiah; Muralitharan, Gangatharan; Albeshr, Mohammed F.; Velmurugan, Gunasekaran (Food and chemical toxicology, 2025)
The cyanobacterial neurotoxin has been implicated in various neurological disorders, posing a potential global health risk. Initial studies revealed alarming levels of β-N-methylamine-l-alanine (BMAA) in cyanobacteria, particularly in symbiotic species, suggesting widespread exposure. This study aimed to validate the efficacy of ultra-fast liquid chromatography (UFLC) technique for the detection and quantification of BMAA in various samples. Derivatizing agents, including 6-aminoquinolyl-N-hydroxysuccinimidyl carbamate (AQC) and N-(2-aminoethyl) glycine (AEG), were synthesized and confirmed via nuclear magnetic resonance (NMR) spectroscopy to enhance the detection of isomeric neurotoxic compounds. Among the samples analyzed cycad seeds, leaves, male cones, cyanobacterial symbionts, coralloid roots, and processed cycad seed flour BMAA and its isomers (2,4-diaminobutyric acid (2,4-DAB) and AEG) were detected in cycad seeds, cyanobacterial symbionts, and coralloid roots. The retention times for L-BMAA, AEG, and 2,4-DAB were 5.4, 5.6, and 6.1 min, respectively. Quantification revealed lower levels of these toxic isomers in seeds compared to high levels in cyanobacterial symbionts. Furthermore, UFLC methods effectively reduced the levels of neurotoxic compounds in cycad seeds to below detectable limits (6 × 103 ng/mL). This study underscores the utility of UFLC method combined with derivatization for the efficient detection and separation of L-BMAA and its isomers, providing a reliable approach for neurotoxin analysis.
Gesehen am 29.10.2025